FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEKERJA PEREMPUAN SEKTOR INFORMAL DI PASAR KEROBOKAN KABUPATEN BADUNG - Pramana, I Putu Ivan Adi; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Women have big role in economic development. The research analyze 1) influence education level of female workers, number family dependents, migration status, work experience the working hours women workers informal sector in Kerobokan Market. 2) female workers' education level, number family dependents, migration status, work experience, work hours spent income of women workers informal sector in Kerobokan Market. 3) work hours spent mediates effect education level women workers, number family dependents, status migration, work experience on income of women workers informal sector in Kerobokan Market. Primary data were 100 samples, using path analysis. The results 1) education level female workers, number family dependents, migration status, work experience have positive effect on working hours women workers in informal sector in Kerobokan Market. 2) education level women workers, number family dependents, migration status, work experience, working hours have positive effect on income of women workers in informal sector in Kerobokan Market. 3) flow working hours mediates education level female workers, number family dependents, migration status, work experience on income of women workers in the informal sector in Kerobokan Market.   Keywords: education level, number of family dependents, migration status, and work experience on working hours, income